Indirect determination of the rate of iron uptake into E. coli ribonucleotide reductase R2 by competition with ferrozine - Umback, Noelle J., author; Norton, Jack R., advisor (Colorado State University. Libraries, 2000)
The rate of iron(II) uptake by apo R2 ribonucleotide reductase from E. coli has been determined. A ferrozine-based competition method for indirectly observing this rate was devised. Ferrozine, an iron(II)-specific ligand, complexes iron from solution at rates competitive with apo R2's iron uptake rate, enabling competition experiments to succeed. The ferrozine-iron complexation reaction (formation of FeIIFz3) was characterized in HEPES buffer at 5.0 °C. The reaction order in ferrozine was found to decrease significantly below third at ferrozine concentrations greater than 800 μM, approaching first at high (≥ 5 mM) ferrozine concentrations. This phenomenon is predicted by the complete derived rate law. The rate of uptake of the first equivalent of ferrous iron into R2 (kapo) has been measured as 1.3(2) x 106 M-1s-1. This step of the reconstitution mechanism appears to occur before the conformational change step, which thus has the same rate constant (8–10 s-1) as the formation of the first observed intermediate in the reconstitution mechanism. Attempts to determine the rate constant for uptake of the second iron equivalent into R2 (kapoFe) were only marginally successful, as the reaction conditions employed precluded an accurate measurement A mechanistic scheme which includes the iron and oxygen uptake steps and the proposed conformational change is offered.
Keywords: chemistry; biochemistry; inorganic chemistry